Posautonomía : notas iniciales para una historia literaria futura - Alves, Wanderlan (2021)
A partir de las principales nociones implicadas en el concepto de posautonomía se analizan algunas figuraciones del campo literario latinoamericano de las últimas décadas en la escritura de César Aira, Roberto Bolaño y Mario Bellatin, y luego se replantea el debate sobre el valor para, por fin, interrogar sobre la posibilidad de una historia literaria pensada desde un régimen posautónomo.
From the main meanings implicated in the concept of post-autonomy, I analyze some figurations within the Latin American literary field of the last decades, present in the writings of César Aira, Roberto Bolaño and Mario Bellatin; later to reinstate the debate on literary value and, finally, to discuss the possibility of a literary history regarded from a post-autonomous regime.
Keywords: Posautonomía; Campo literario latinoamericano; Valor; Crítica; Historiografía literaria; Post-autonomy; Latin American Literary Field; Literary Value; Criticism; Literary Historiography